Graphene materials in antimicrobial nanomedicine : current status and future perspectives - Karahan, Hüseyin Enis (2020)
Graphene materials (GMs), such as graphene, graphene oxide (GO), reduced GO (rGO), and graphene quantum dots (GQDs), are rapidly emerging as a new class of broad‐spectrum antimicrobial agents. This report describes their state‐of‐the‐art and potential future covering both fundamental aspects and biomedical applications. First, the current understanding of the antimicrobial mechanisms of GMs is illustrated, and the complex picture of underlying structure–property–activity relationships is sketched. Next, the different modes of utilization of antimicrobial GMs are explained, which include their use as colloidal dispersions, surface coatings, and photothermal/photodynamic therapy agents. Due to their practical relevance, the examples where GMs function as synergistic agents or release platforms for metal ions and/or antibiotic drugs are also discussed. Later, the applicability of GMs in the design of wound dressings, infection‐protective coatings, and antibiotic‐like formulations (“nanoantibiotics”) is assessed. Notably, to support our assessments, the existing clinical applications of conventional carbon materials are also evaluated. Finally, the key hurdles of the field are highlighted, and several possible directions for future investigations are proposed. We hope that the roadmap provided here will encourage researchers to tackle remaining challenges toward clinical translation of promising research findings and help realize the potential of GMs in antimicrobial nanomedicine.